Oral Pregabalin in Cardiac Surgery: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Wang, Xian-xue (Biomed Res Int, 2021)
BACKGROUND: Pregabalin has received wide clinical attention as a new type of analgesic. We undertake a systematic review and meta-analysis to evaluate the effect of pregabalin on postoperative pain in patients undergoing cardiac surgery. METHODS: We searched PubMed, Embase, and Cochrane Library (from inception to July 2020) for eligible studies. The primary outcomes were the total morphine consumption at 24 h. A secondary outcome was intraoperative fentanyl consumption, extubation time postoperative, and length of stay in hospital. We calculated pooled weighted mean difference (WMD) or odds ratio (OR) and 95% CIs using random- or fixed-effects models. RESULTS: Seven trials involving 463 patients were listed. Meta-analysis showed that the total morphine consumption at 24 h in the pregabalin group was significantly less than the control group (WMD: -5.44, 95% CI: -10.42–0.46, P = 0.03). We found that there is no significant difference between the two groups in intraoperative fentanyl consumption. Compared with the control group, the length of stay in hospital in the pregabalin group was significantly shorter (WMD = -0.87, 95% CI: -1.42−0.32, P = 0.002). And we found that there were no significant differences between the two groups in extubation time (WMD: 17.24, 95% CI: -24.36−58.84, P = 0.42). CONCLUSIONS: Oral pregabalin for cardiac surgery patients can effectively reduce the patient's 24-hour morphine consumption after surgery, shorten the patient's hospital stay, and is more conducive to early postoperative recovery.